Who Can Speak for Whom? Using Counter-Storytelling to Challenge Racial Hegemony - Lisa R. Merriweather Hunn; Talmadge C. Guy; Elaine Mangliitz (Adult Education Research Conference, 2006)
Dialogues of socially significant forms of human difference such as race are constrained by hegemony. Critical Race Theory’s counter-storytelling is explored as a means of challenging the majoritarian stories that reinforce racial hegemony in the dominant discourse.
Keywords: Critical Race Theory; Counter Storytelling; Racist Discourses; Positionality